Conversion therapy in gastric cancer: experience at Instituto Nacional de Cancerología de Colombia - Briceño Morales, Clara; Pinilla Morales, Raúl E.; Oliveros Wilches, Ricardo; Navia, Helena F. (Revista Argentina de Cirugía, 2026)
Background: Gastric cancer (GC) represents a public health problem in Colombia and worldwide. Since most patients are at advanced stages at the time of diagnosis, it is necessary to develop management strategies as conversion therapy (CT). Objective: The aim of this study was to estimate the results of CT for treating patients with advanced and GC at Instituto Nacional de Cancerología de Colombia (INC). Material and methods: We included patients with incurable gastric cancer who underwent induction chemotherapy and intended curative surgery between 2010 and 2021. The clinical and pathological data and survival of the patients included were retrospectively reviewed. Overall survival (OS) was calculated from the time of initiation of chemotherapy until the date of death. Survival functions were estimated using the life table and Kaplan-Meier methods, and survival curves at 3 and 5 years were constructed. Results: 23 patients were analyzed; mean age was 56 years, and 17 (74%) were men. The most common criterion indicating unresectability was a T4b tumor in 13 cases (56.5%). All the patients underwent CT. Median follow-up was 28 months. Eleven patients developed disease recurrence (52%). Median survival was 41.2 months, and 3- and 5-year OS was 57.7% and 38.5%, respectively. Conclusions: CT provided an acceptable OS rate for selected patients with incurable advanced GC. This strategy requires an adequate selection of patients and multidisciplinary management in reference oncology centers